Excitonic states in Narrow armchair graphene nanoribbons on gold surfaces - Bronner, Christopher; Gerbert, David; Broska, Alexander; Tegeder, Petra (The journal of physical chemistry. C, Energy, materials, and catalysis, 2016)
Narrow graphene nanoribbons (GNRs) exhibit electronic and optical properties that are not present in extended graphene. Most importantly, they possess band gaps in the order of a few electron volts, which has been subject to numerous studies. Here we report on the experimental observation of exctionic states in the band gap of N = 7 armchair GNRs (7-GNR) on Au(111) and Au(788) using energy- and angle-resolved two-photon photoemission spectroscopy. Thereby, an exciton binding energy in the 7-GNR on Au(111) of 160 ± 60 meV has been determined. On the stepped Au(788) surface, the exciton binding energy is in the same range.